Hepatopulmonary syndrome associated with long-term use of ado-trastuzumab emtansine (T-DM1) for treatment of HER2-positive metastatic breast cancer - a case report and series - O’Sullivan, Ciara C.; Higgins, Alexandra S.; Alkurashi, Adham K.; Ahluwalia, Vaibhav; Taraba, Jodi L.; McKie, Paul M.; Kamath, Patrick S.; Iyer, Vivek N.; Haddad, Tufia C. (Frontiers in Oncology, 2024)
BackgroundThe advent of antibody-drug conjugates (ADCs) represents a landmark advance in cancer therapy, permitting targeted delivery of a potent cytotoxic agent to tumor cells with minimal damage to surrounding cells. Although ADCs can induce sustained therapeutic responses in heavily pretreated patients, they can also cause significant toxicity and thus require careful monitoring. The prototype ADC, ado-trastuzumab emtansine (T-DM1) is comprised of a humanized, monoclonal human epidermal growth factor receptor 2 (HER2)-directed antibody, trastuzumab, linked to the cytotoxic agent, DM1, and is used for the treatment of early-stage and advanced HER2-positive breast cancer. Liver toxicities, including transaminitis and nodular regenerative hyperplasia resulting in portal hypertension have been described. We report a case series of four patients who developed hepatopulmonary syndrome (HPS) during treatment with T-DM1. HPS is characterized by hypoxemia, portal hypertension, and intrapulmonary shunting, and it can be associated with severe hypoxic respiratory failure. HPS secondary to noncirrhotic portal hypertension occurring with long-term exposure to T-DM1 has not previously been reported.Case series presentationFour patients who received T-DM1 in our institutional cohort (n=230) developed HPS, which can be associated with severe hypoxic respiratory failure. Each patient diagnosed with HPS received >50 doses of T-DM1. Only one patient at diagnosis had resting hypoxia, while the other three patients became hypoxic with exertion only. Discontinuation of T-DM1 led to clinical improvement in hypoxia in three of the four patients. The spectrum of liver injury that occurs with long-term use of T-DM1 remains incompletely defined.ConclusionsAs T-DM1 is approved for use in the management of early-stage operable and advanced breast cancer, awareness of HPS as a potential complication of long-term administration of T-DM1 is necessary. The emergence of dyspnea alone or combined with low oxygen saturation and signs of hypoxemia (clubbing or elevated hemoglobin) should raise clinical suspicion and prompt evaluation for HPS. Cancer care team members should be vigilant regarding the potential for new and serious side effects associated with novel targeted therapies, which may emerge years beyond initial regulatory approval.